Examining the effects of green revolution led agricultural expansion on net ecosystem service values in India using multiple valuation approaches. (1st January 2021) - Sannigrahi, Srikanta; Pilla, Francesco; Zhang, Qi; Chakraborti, Suman; Wang, Ying; Basu, Bidroha; Basu, Arunima Sarkar; Joshi, P.K.; Keesstra, Saskia; Roy, P.S.; Sutton, Paul C.; Bhatt, Sandeep; et al.
Abstract: Ecosystem Services (ESs) are bundles of natural processes and functions that are essential for human well-being, subsistence, and livelihoods. The 'Green Revolution' (GR) has substantial impact on the agricultural landscape and ESs in India. However, the effects of GR on ESs have not been adequately documented and analyzed. This leads to the main hypothesis of this work – ' the incremental trend of ESs in India is mainly prompted by GR led agricultural innovations that took place during 1960 - 1970 '. The analysis was carried out through five successive steps. First, the spatiotemporal Ecosystem Service Values (ESVs) in Billion US for 1985, 1995, and 2005 were estimated using several value transfer approaches. Second, the sensitivity and elasticity of different ESs to land conversion were carried out using coefficient of sensitivity and coefficient of elasticity. Third, the Geographically Weighted Regression model was performed using five explanatory factors, i.e., total crop area, crop production, crop yield, net irrigated area, and cropping intensity, to explore the cumulative and individual effects of these driving factors on ESVs. Fourth, Multi-Layer Perceptron based Artificial Neural Network was employed to estimate the normalized importance of these explanatory factors. Fifth, simple and multiple linear regression modeling was done to assess the linear associations between the driving factors and the ESs. During the observation periods, cropland, forestland and water bodies contributed to 80%–90% of ESVs, followed by grassland, mangrove, wetland and urban built-up. In all three evaluation years, the highest estimated ESVs among the nine ES categories was provided by water regulation, followed by soil formation and soil-water retention, biodiversity maintenance, waste treatment, climate regulation, and greenhouse gas regulation. Among the five explanatory factors, total crop area, crop production, and net irrigated area showed strong positive associations with ESVs, while cropping intensity exhibited a negative association. Therefore, the study reveals a strong association between GR led agricultural expansion and ESVs in India. This study suggests that there should be an urgent need for formulation of rigorous ecosystem management strategies and policies to preserve ecological integrity and flow of uninterrupted ESs and to sustain human well-being. Highlights: The ecosystem service values (ESVs) of India is estimated from 1985 to 2005. The total ESVs in India is significantly increased due to the green revolution. Total crop area and crop production factors are highly correlated with increased ESVs. Substantial forest ESVs has been lost due to acute forest degradation and deforestation. The forest, wetlands, and water bodies ESV's reveal most negative elasticity and high sensitivity to land use changes.